Employee Relations and the Quaker Employers Conference of 1918: The Cadbury Company. Issue 2 (December 2019) - Kimberley, John
Abstract : This article considers the part Quaker employers played in promoting new and different ways of practising employee relations early in the twentieth century. After providing background information to the events leading up to the first Quaker Employers Conference of 1918, attention shifts to the Conference itself. The Conference provided a platform for Labour movement activists to state their case before Quaker employers went on to discuss their pressing concerns. The final section of the paper uses the Cadbury company as a case study to examine the ways in which one Quaker company was prepared to 'experiment' with new and different ways of conducting employee relations. The article concludes by arguing that the Cadbury company was being used as a model of good practice to which other Quaker employers might aspire.